THE EFFECT OF CARTOON ANIMATION INTEGRATED WITH TPR ON STUDENTS’ VOCABULARY MASTERY AND LEARNING MOTIVATION AT SD ISLAM KHAIRA UMMAH - Fatma; Yuli Tiarina (University of Kuningan, 2026)
Students still face difficulties in vocabulary mastery and learning motivation, indicating the need for more engaging instructional strategies. This study aimed to examine the effect of cartoon animation integrated with Total Physical Response (TPR) on students’ vocabulary mastery and learning motivation. This research employed a quasi-experimental pre- and post-test design. The study population consisted of 101 third-grade students at SD Islam Khaira Ummah. The sample included 22 students from class 3C as the control group and 24 students from class 3D as the experimental group. The experimental group was taught using cartoon animation integrated with TPR, while the control group received conventional instruction. A vocabulary test and a learning motivation questionnaire were used to collect the data. The results showed that the experimental group achieved a higher mean post-test score in vocabulary mastery (M = 86.25) compared to the control group (M = 80.00), with a statistically significant difference (t = 2.204, df = 44, p = 0.033). Similarly, the experimental group demonstrated higher learning motivation (M = 82.67) than the control group (M = 76.50), with a significant difference (t = 3.226, df = 44, p = 0.020). These findings indicate that integrating cartoon animation with TPR can positively influence students’ vocabulary mastery and learning motivation. Therefore, this approach may be considered as an alternative instructional strategy for teaching vocabulary to elementary school students.